2021
DOI: 10.1186/s40814-021-00768-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving nursing documentation for surgical patients in a referral hospital in Freetown, Sierra Leone: protocol for assessing feasibility of a pilot multifaceted quality improvement hybrid type project

Abstract: Background There is an urgent need to improve quality of care to reduce avoidable mortality and morbidity from surgical diseases in low- and middle-income countries. Currently, there is a lack of knowledge about how evidence-based health system strengthening interventions can be implemented effectively to improve quality of care in these settings. To address this gap, we have developed a multifaceted quality improvement intervention to improve nursing documentation in a low-income country hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Our study demonstrated enablers and barriers to the improvement of pain care in LMICs and will inform similar QIC initiatives and evaluations proposed for the future [37]. Future QICs should be dedicated to long-term commitment and collaboration with local experts, as fostering these relationships cannot be rushed and are the foundation to sustained improvement.…”
Section: Discussionmentioning
confidence: 56%
“…Our study demonstrated enablers and barriers to the improvement of pain care in LMICs and will inform similar QIC initiatives and evaluations proposed for the future [37]. Future QICs should be dedicated to long-term commitment and collaboration with local experts, as fostering these relationships cannot be rushed and are the foundation to sustained improvement.…”
Section: Discussionmentioning
confidence: 56%
“…Although these figures increased overall, the increase was sharper in the intervention unit. Clinical documentation is an essential part of nursing care [ 58 ], by facilitating access to valid patient data and enabling healthcare providers to make a timely evaluation and deliver appropriate follow-up [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,17 Acceptability, appropriateness, feasibility, adoption, fidelity, and sustainability were utilized as measures of early implementation success. 13,20,21 The definitions, measurement tools, and rigorous a priori definitions of success are illustrated in Table 3. We used acceptability as the primary outcome for assessing success based on use in prior work.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…22,23 Each measure of implementation success is based upon previously utilized and validated survey instruments. 20,21,24 The Acceptability of Intervention Measure (AIM), Intervention Appropriateness Measure (IAM), and Feasibility of Intervention Measure (FIM) were utilized to measure acceptability, appropriateness, and feasibility, respectively (Appendix A). The AIM, IAM, and FIM have been shown to have strong psychometric properties, including validity, reliability, and structural invariance.…”
Section: Outcome Measuresmentioning
confidence: 99%